2012
DOI: 10.1259/bjr/91771639
|View full text |Cite
|
Sign up to set email alerts
|

Combining diffusion-weighted MRI with Gd-EOB-DTPA-enhanced MRI improves the detection of colorectal liver metastases

Abstract: Objectives: To compare the diagnostic accuracy of gadolinium-ethoxybenzyldiethylenetriaminepentaacetic acid (Gd-EOB-DTPA)-enhanced MRI, diffusion-weighted MRI (DW-MRI) and a combination of both techniques for the detection of colorectal hepatic metastases. Methods: 72 patients with suspected colorectal liver metastases underwent Gd-EOB-DTPA MRI and DW-MRI. Images were retrospectively reviewed with unenhanced T 1 and T 2 weighted images as Gd-EOB-DTPA image set, DW-MRI image set and combined image set by two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 23 publications
1
59
0
Order By: Relevance
“…7), was noteworthy. Previous studies have suggested that the combination of DWI with hepatospecific contrast-enhanced sequences may improve our ability to detect colorectal liver metastases [13][14][15][16][17][18]. However, these data were obtained in small, heterogenous series.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…7), was noteworthy. Previous studies have suggested that the combination of DWI with hepatospecific contrast-enhanced sequences may improve our ability to detect colorectal liver metastases [13][14][15][16][17][18]. However, these data were obtained in small, heterogenous series.…”
Section: Discussionmentioning
confidence: 97%
“…one-or two-stage hepatectomy). In recent years, however, the efficacy of the newer cytotoxic agents has expanded the use of systemic chemotherapy in the preoperative setting before liver resection in both unresectable and resectable patients [14][15][16]. As a consequence, post-chemotherapy evaluation has become a routine challenge.…”
Section: Discussionmentioning
confidence: 99%
“…(21) However, there is mounting evidence in the literature of the superior sensitivity of MR imaging in detecting and characterising liver lesions compared with CT, particularly when combined with the use of a specific hepatobiliary contrast agent and DWI. (22) While most of the data relates to colorectal cancer liver metastasis, MR imaging has been shown to be equally useful with other malignancies. (18) This study supports the findings from previous studies that suggested increased detection of liver metastases in patients with pancreatic cancer on MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…While several articles and 1 meta-analysis show that combining DW-MRI with gadoxetic acid-enhanced MRI significantly improves the detection of colorectal liver metastases [43][44][45][46] , such studies are missing in NET.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%